The Dynamics of Liquidity-adjusted Capital Asset Pricing Model in SubSahara Africa: Evidence from Ghana - Hongxing, Yao; Duduchoge, Solomon (IJRDO - Journal of Applied Management Science, 2017)
This paper estimates the systematic liquidity risk in Ghana using the conditional version ofliquidity–adjusted capital asset pricing model in an emerging Ghana’s market. We find thatco-movements between stock returns and individual liquidity, market liquidity as well asmarket returns react differently under different market conditions. Applying the size effecton liquidity, it is evidence that the size effect is stronger for smaller firms in Ghana than forlarger firms. While the effect of the recent financial crisis do not exhibit a strong influence onthe market, it effect is stronger in the down market than the up market. Finally, we explorethe reasons behind the poor performance of stock in Ghana and concluded that lack oftransparency and protection for firms are some of the problems.